2020
DOI: 10.15252/embr.202050071
|View full text |Cite
|
Sign up to set email alerts
|

20,000 picometers under the OMM: diving into the vastness of mitochondrial metabolite transport

Abstract: The metabolic compartmentalization enabled by mitochondria is key feature of many cellular processes such as energy conversion to ATP production, redox balance, and the biosynthesis of heme, urea, nucleotides, lipids, and others. For a majority of these functions, metabolites need to be transported across the impermeable inner mitochondrial membrane by dedicated carrier proteins. Here, we examine the substrates, structural features, and human health implications of four mitochondrial metabolite carrier familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 170 publications
0
31
0
Order By: Relevance
“…Mitochondria function as a metabolic hub that controls physiology and disease by balancing the concentrations of multiple metabolites and essential elements ( Baker et al, 2017 ; Martínez-Reyes and Chandel, 2020 ). The MCF proteins play a critical role in regulating the import and export of these substrates ( Cunningham and Rutter, 2020 ; Palmieri et al, 2020 ), and have been duplicated and specialized over evolutionary time to selectivity recognize and transport highly similar substrates. However, gene duplication has allowed for the retention of some carriers with multiple substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria function as a metabolic hub that controls physiology and disease by balancing the concentrations of multiple metabolites and essential elements ( Baker et al, 2017 ; Martínez-Reyes and Chandel, 2020 ). The MCF proteins play a critical role in regulating the import and export of these substrates ( Cunningham and Rutter, 2020 ; Palmieri et al, 2020 ), and have been duplicated and specialized over evolutionary time to selectivity recognize and transport highly similar substrates. However, gene duplication has allowed for the retention of some carriers with multiple substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial carrier family (MCF/SLC25) proteins comprise the largest family of mitochondrial inner membrane (IM) proteins and are responsible for transporting numerous substrates, including Krebs cycle intermediates, nucleoside di- and triphosphates for energy metabolism and nucleotide replication, amino acids for degradation or maintenance of the urea cycle, and essential metals such as copper (Cu) and iron ( Palmieri et al, 2020 ; Cunningham and Rutter, 2020 ). Structurally, MCF transporters consist of a conserved fold with three repeats that contain two transmembrane helices connected by a short α-helical loop ( Robinson et al, 2008 ; Ruprecht and Kunji, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other transmembrane protein families, such as the sideroflexin family (SFXN), the mitochondrial pyruvate carrier (MPC1/2), certain ATP-binding cassette transporter (ABCB) isoforms, and splice variants of other solute carriers (SLCs), also contribute to mitochondrial transport. Excellent reviews of our current knowledge of mitochondrial transporters can be found elsewhere [ 205 , 206 , 207 ]. Recent progress has been made on the identification of mitochondrial amino acid carriers, including those that transport serine (SFXN1/3), glutamine (mitochondrial targeted SLC1A5 variant), and branched chain amino acids (SLC25A44) [ 208 , 209 , 210 ].…”
Section: Mitochondrial Amino Acid Carriersmentioning
confidence: 99%
“…The mitochondrial pyruvate carrier (MPC) belongs to an unrelated protein family and functions as a hetero-dimer that requires both subunits for carrier activity [ 6 , 7 ]. The sideroflexin family constitutes a third metabolite carrier family, members of which have recently been discovered to function as serine transporters in one-carbon metabolism [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%